THE PROCESS OF LEARNING TERMINOLOGY IN ENGLISH AND ITS APPLICATION IN COLLOQUIAL SPEECH - Rasulova, Zukhra (Журнал иностранных языков и лингвистики, 2023)
The article is about the relevance of this material is determined by the need to develop principles for the implementation of a communicative-cognitive approach to teaching terminological vocabulary, as well as the need to develop an effective set of exercises for mastering terminological vocabulary for students of non-linguistic universities. There should be a development of complex exercises for the formation and improvement of terminological skills and abilities necessary for the implementation of professionally oriented foreign language communication. The other thing is that completely new opportunities open up if it is in connection with the advent of affordable computer hardware and software if an instructor fulfills such programs with terminology that students should master. Students can demonstrate their interest both in IT mastering and professional (terminology) language learning desire in this case.